The Advantages and Disadvantages of English Learning For Early Childhood Education in Indonesia - Ayu Paramita Sari (Universitas Indo Global Mandiri, 2020)
ABSTRACTEveryone is only able to speak one language, the language they acquired naturally and grow with that, but it does not close the possibility to speak more than one language with learn. Language is essentially a means of communication among the members of a society. Language becomes very important because everything that humans do with each other is with this media. Foreign language of course is different from the mother tongue. Whether a grammar, the use of letters and how to read that is different. And when a child is told to learn thousands of foreign language vocabulary, of course it will make them stressful because how to spell and pronounce it is different from the mother tongue. But when someone does an adaptation in the social environment, then someone will use language that is adapted to the situation and conditions. Indonesia is a unitary country and also called as multicultural country, because Indonesia has a variety of languages and cultures. Indonesia still has one language called as Indonesia Language which is used as a national language to unite various regional languages. English, which is a foreign language in Indonesia, has a big role for Indonesia itself. Learning language in the early childhood is a good and also bad in the same time.Keywords : Language, Foreign Language, Early Childhood, Mother TongueABSTRAKSetiap orang hanya dapat berbicara satu bahasa, bahasa yang mereka peroleh secara alami dan besar dengannya, tetapi tidak menutup kemungkinan untuk berbicara lebih dari satu bahasa dengan belajar. Bahasa pada dasarnya adalah alat komunikasi di antara masyarakat. Bahasa menjadi sangat penting karena semua yang manusia lakukan satu sama lain adalah dengan media ini. Bahasa asing tentu saja berbeda dengan bahasa ibu. Baik tata bahasa, penggunaan huruf dan cara membaca yang berbeda. Dan ketika seorang anak disuruh belajar ribuan kosakata bahasa asing, tentu saja itu akan membuat mereka stres karena cara mengeja dan mengucapkannya berbeda dari bahasa ibu. Tetapi ketika seseorang melakukan adaptasi di lingkungan sosial, maka seseorang akan menggunakan bahasa yang disesuaikan dengan situasi dan kondisi. Indonesia adalah negara kesatuan dan juga disebut sebagai negara multikultural, karena Indonesia memiliki beragam bahasa dan budaya. Indonesia masih memiliki satu bahasa yang disebut sebagai Bahasa Indonesia yang digunakan sebagai bahasa nasional untuk menyatukan berbagai bahasa daerah. Bahasa Inggris, yang merupakan bahasa asing di Indonesia, memiliki peran besar bagi Indonesia sendiri. Belajar bahasa pada anak usia dini adalah hal yang baik dan juga buruk pada saat yang bersamaan.Kata kunci : Bahasa, Bahasa Asing, Pendidikan usia dini, Bahasa Ibu